The Implications of Crowdfunding on News Production and Distribution Practices in Indonesia's Online Media - Humeira, Bintan; Aji, Rizka Sasongko (Jurnal Studi Jurnalistik, 2024)
This article investigates the crowdfunding journalism model and its implications for the news production and distribution of Project Multatuli (PM), the first crowdfunding media in Indonesia. Therefore, this research utilizes a crowdfunding journalism perspective, a qualitative approach study, and triangulation methods for data collection (in-depth interviews, participant observation, and documentation). The results showed the following findings: First, PM uses a combination funding model of crowdfunding and donor agencies, rather than hybrid funding based on a traditional business model that relies on media owners and advertising. This combination funding model aims to be free from pressure from media owners as investors and profit orientation from advertising revenue. Second, PM creates a transparent, participatory and collaborative co-creation process with its members in content production. Third, PM 'resists' the logic of algorithms through clickbait to increase digital traffic which has implications for the speed and superficiality of coverage.  It is a form of PM's dedication to investigative journalism that is committed to in-depth coverage in order to maintain the credibility of the content. Lastly, PM distributes content through national, local and international media networks under creative license. Thus, the distribution strategy is more aimed at expanding the reach of literacy to the general public, rather than just increasing readership.